Review on the control of ice nucleation by ultrasound waves, electric and magnetic fields - Dalvi-Isfahan, Mohsen; Hamdami, Nasser; Xanthakis, Epameinondas; LeBail, Alain (My University, 2017)
Freezing is the most popular and widely used food preservation method of the modern times. The freezing process of food matrices is related to their high water content and its metamorphoses into ice on cooling. The final quality of the frozen product is highly depended on the ice crystal morphology because it can cause irreversible damage on the microstructure of the food matrix. Supercooling and ice nucleation temperature need to be controlled both in suppressing and inducing the solidification to improve technological processes such as freeze drying, freeze concentration, cryopreservation, ice formation and cold-energy storage both in food industry and domestic preservation. However, the mechanism of freezing is not yet well known and it is affected by several factors. Several emerging technologies have been recently proposed for ice nucleation control during freezing. This review article is focused on the alternative freezing methods such as ultrasound waves, magnetic, electric, and electromagnetic field assisted freezing. In addition, the properties, mechanism of action and possible applications of electrofreezing are extensively discussed.
Keywords: Electric fields; Magnetic fields; Electromagnetic; Ultrasound; Food; Freezing